ABORSI JANIN CACAT DALAM PERSPEKTIF HUKUM ISLAM - Zein, Fuad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2017)
Abortion has generally been considered cruel, inhumane, and contrary to religious law and doctrine. However, the law of abortion in particular needs to be studied in more depth, as there are various causes, not only one form, that underlie it.This paper examines how abortion is done due to indications of fetal defects according to Islamic law. This research is a type of normative legal research that is prescriptive, because this research is a scientific research to find the truth based on scientific logic from the side of law, using the approach of fiqh. The types of legal materials that the author uses are primary and secondary legal materials. The primary legal materials include the Qur'an, al-Hadith, and the fiqh books, while the secondary legal materials used are the literature that is in accordance with the object of study including Law no. 36 Year 2009 on Health. Data analysis technique is used with deductive logic. Based on the study findings, the conclusions are, first, the law of abortion is haram though in various levels in accordance with the development of fetal life. Second, Medical advancement has now been able to detect fetal damage before the age of four months. It is not considered accurate if the doctor makes the assumption that after birth the baby will experience a blemish such as blindness, deafness, or mute and that those defects are considered a cause that permits abortion. Such defects are actually disabilities that have been known in the wider community throughout human life and carried by many people. Third, nevertheless, in the first 40 days, and before the age of the fetus reaching 120 days in the womb, the fetus is in the phase of a clot of flesh and blood. If a trusted doctor determines that the fetus has a malformed disability and it cannot be cured, and if left alive, the future conditions will become a problem for him and for his family. In this condition, abortion may be permitted, according to the parents’ request.Kata kunci: aborsi, janin cacat, Hukum Islam